Biomarkers and cellular biology in perioperative medicine - Larmann, Jan; Luedi, Markus M. (Cells, 2022)
Surgical procedures alter tissue integrity; are associated with pain and activation of the sympathetic nervous system; and sometimes, cause exposure to foreign materials used during the surgery or implanted perioperatively [...]
Gesehen am 11.05.2022